Tratamento de pacientes com estomatite protética: uso de laser de baixa intensidade - Raphaelle Menezes da Frota Ponte (2018)
Stomatitis under prosthesis is the common disorder found in oral mucosa in patients with total prosthesis. It is asymptomatic, however, and may present with rare symptomatology, which includes: pain, halitosis, burning and pruritus. This study aimed to compare patients with stomatitis, treated with low intensity laser and with antifungal. The study was carried out with 20 individuals over 50 years of age, users of superior removable total dentures (PT), among those who sought treatment to replace their PT at the Sérgio Arouca Dental Specialty Center, in the city of Sobral - CE. The analysis of the data was done through the photographic registry evaluation and measured by the Budtz-Jorgensen index. For the study the patients were divided into two groups. The first group with 10 patients was irradiated with low intensity diode laser one application per day and 48 hour interval between each application totaling 3 applications. In the second group of 10 patients 10 ml of antifungal mycostatin 100,000 IU / ml was prescribed 3 times daily for 14 days. The results of the study revealed that the conventional treatment with Nystatin mouthwash showed an effective result in some patients; in the group that used the laser, no change in the clinical aspect of the lesions was recorded immediately; observed a reasonable improvement of the appearance of the lesions. Regarding the absence of burning or swelling, there was no reference to these factors.